OWEFE—open modeling framework for integrated water, energy, food, and environment systems. (1st March 2023) - Fleischmann, Julian; Blechinger, Philipp; Ribbe, Lars; Nauditt, Alexandra; El Achkar, Jean H; Tiwari, Kapil; Kuleape, Richmond; Platzer, Werner
Abstract: The integrated approach to managing the fundamental resources for human life, namely, water, energy, food, and the environment as their irreplaceable foundation, presents a profound opportunity for sustainable development. However, despite their huge potential, integrated water, energy, food, and environment systems (iWEFEs) are rarely put into practice because of, among others, complexity and a lack of uniform and openly available models to describe, configure and simulate such systems. To fill this gap, we present the open modeling framework for integrated water, energy, food, and environment systems (OWEFEs) based on the open energy modeling framework. OWEFE follows an open, cross-sectoral, and modular design approach to address crucial challenges for the project development of iWEFEs. In this study, we apply OWEFE for the first time to model a wastewater biogas system and an agrivoltaics system. The results of the OWEFE-based models are in the range of a conventional approach respectively of on-site measurements indicating the framework's capability to model diverse iWEFEs. The wide application of the framework can improve the assessment, planning, and configuration of iWEFEs for sustainable and integrated infrastructure development.